2018
DOI: 10.5539/ies.v11n3p77
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on the Relationship between Creativity and Processing Speed for Gifted Children

Abstract: This study explored the relationship between processing speed and five dimensions of creativity, which were fluency, originality, elaboration, abstractness of titles, and resistance to premature closure (RPC). It is the first empirical study that examines this relationship, also relating it to gender and level of giftedness. Data came from 133 gifted students at grades one through four in three private schools in Istanbul, Turkey. Creativity was measured through the Torrance Test of Creative Thinking -Figural.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
1
3
0
2
Order By: Relevance
“…Our recommendation is that both verbal and figural tasks be used to screen students for special programs (e.g., gifted student programs), as using both mediums seem to capture a fuller spectrum of gender strengths. Finally, the comparison between gifted and nongifted samples showed that both gifted females and nongifted females outperformed gifted males and nongifted males, although the magnitude of the effect size was larger in gifted females than gifted males, supporting some previous giftedness and DT findings (e.g., Bahar & Ozturk, 2018).…”
Section: Gender Differences In Meanssupporting
confidence: 74%
“…Our recommendation is that both verbal and figural tasks be used to screen students for special programs (e.g., gifted student programs), as using both mediums seem to capture a fuller spectrum of gender strengths. Finally, the comparison between gifted and nongifted samples showed that both gifted females and nongifted females outperformed gifted males and nongifted males, although the magnitude of the effect size was larger in gifted females than gifted males, supporting some previous giftedness and DT findings (e.g., Bahar & Ozturk, 2018).…”
Section: Gender Differences In Meanssupporting
confidence: 74%
“…Moreover, Bahar and Ozturk (2018) examined the relationship between processing speed and creativity, identifying a positive relationship between processing speed and both fluency and originality among gifted boys but not gifted girls. Motivational factors might also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Lo anterior, se corroboró en la etapa Post-test en donde se encontró que los participantes incrementaron su flexibilidad de pensamiento, sus ideas fueron originales, mejoraron su comprensión verbal, razonamiento perceptual, velocidad de procesamiento, memoria, motivación y su autopercepción como estudiantes. Lo anterior, concuerda con otros estudios que han observado beneficios en las capacidades de los estudiantes que participaron en programas de enriquecimiento (Bahar & Ozturk, 2018;Chávez, 2008;Chávez et al, 2009;Howie, 2015;Klimenko y Botero, 2016). En este sentido, cobra relevancia lo señalado por Sternberg (1998Sternberg ( , 2005, Golle et al (2019), Howie (2015), Ushiñahua y Vílchez (2016), quienes mencionaron que la adquisición y consolidación de un conjunto de destrezas, permite el dominio de distintas áreas académicas y favorece el aprendizaje.…”
Section: Figuraunclassified
“…dados para agruparlos en una categoría) y percepción analítica (estrategias para la integración, síntesis de las partes de un todo, de acuerdo con ciertos objetivos).Con base en lo antes descrito, en la presente investigación se consideró pertinente retomar las propuestas de Tzuriel y Feuerstein (1992) y deDuarte (2001); la primera, se ha empleado principalmente en población que presenta bajos niveles cognitivos, y la segunda es una alternativa para favorecer la creatividad(Bahar & Ozturk, 2018;Klimenko y Botero, 2016). Se hicieron adaptaciones de acuerdo con el perfil de los estudiantes sobresalientes, y en este estudio se presentan los hallazgos de esta alternativa educativa.…”
unclassified